(untitled) (Sociologisk Forskning, 1999)
Not from love alone. Power and the division of housework. A recent Swedish study by Ahrne & Roman (1997) shows that married and cohabiting women often feel discontent with their male partner’s contribution to housework, while married and cohabiting men commonly feel quite satisfied with the gendered division of housework. This indicates that spouses have different interests and preferences when negotiating the division of housework. The study also indicates that conflicts are frequent in households where the male partner’s share of the housework is small or insignificant. The present article starts analysing such conflicts by applying an episodic concept of power, the argument being that men’s satisfaction and women’s discontent with a gendered division of housework, implies male domination. Bringing the concept of ”gender order” into the analysis, it goes on to maintain that male marital power is best explained by men’s greater access to economic and normative resources. Finally, it is argued that high levels of conflicts between spouses, while signs of male domination, also indicate the weakening of male power. Female economic independence, together with declining male authority, has created a situation of relative deprivation for women, i.e. increasing aspirations for equality, in a situation where most women still do the main part of housework. This situation explains not only high levels of conflicts between spouses, but also points to changing gender relations.